ChemInform Abstract: SNAr versus Buchwald—Hartwig Amination/Amidation in the Imidazo[2, 1‐b][1, 3, 4]thiadiazole Series. Issue 11 (February 2016) - Copin, Chloe; Massip, Stephane; Leger, Jean‐Michel; Jarry, Christian; Buron, Frederic; Routier, Sylvain
Abstract: Amination of the heterocyclic skeleton is first carried out under conditions A).